RESPONSIVITAS PEMERINTAH DAERAH KABUPATEN SIAK DALAM PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI KECAMATAN TUALANG KABUPATEN SIAK TAHUN 2018 - Karlila Siamisury; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
In answering the problem of community housing, the government has prepared various national programs to help Low-Income Communities to get livable houses. Of the many government programs regarding housing for low-income families, there is a new program issued at the end of 2015, namely the Self-Help Housing Stimulant Assistance Program (BSPS). Self-Help Housing Stimulant (BSPS) is a program to increase Low-Income Community (MBR) initiatives in building or improving the quality of houses along with infrastructure, facilities, and utilities.The purpose of this study is to determine the responsiveness of the Siak Regency Government and determine the factors that affect the responsiveness of the Siak Regency Government in the Self-Help Housing Stimulant Assistance Program (BSPS) in Tualang District, Siak Regency in 2018. The theory used is the Responsiveness theory. The research location was carried out in the Public Works, Spatial Planning, Public Housing and Settlement Areas and Tualang District, Siak Regency. This research uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.The results of this study concluded that complaints from the community regarding BSPS were still not well responded to, especially by Field Facilitators, this was due to the lack of number of Field Facilitators provided. Then various actions taken by the Dinas in providing satisfaction to the community, namely providing guidance in the form of socialization, training, technical guidance, supervision, and assistance. Furthermore, community involvement in resolving complaints about BSPS problems already exists, this can be seen from the community who first solve their problems together with their group members in a family manner. However, the problem with the Self-Help Housing Stimulant Assistance Program (BSPS) is not entirely the fault of the Government but there is still a lack of public understanding regarding the Self-Help Housing Stimulant Assistance Program (BSPS) itself. Keywords: Responsiveness, Self-Help Housing Stimulant (BSPS)